Role of vascular endothelial dysfunction and metabolic eprogramming of immune cells in the development and ogression of atherosclerosis - Zhili, Guo; Zhimin, Guan; Nenghua, Zhang (Frontiers in Physiology, 2025)
The pathogenesis of atherosclerosis (AS) involves a complex interaction between vascular endothelial dysfunction and immunometabolic disorders. During the process of AS, vascular endothelial cells (ECs) are affected by multiple environmental stimuli (oxidative stress, shear force abnormalities) and undergo endothelial dysfunction, which is mainly manifested by a shift in energy metabolism toward aerobic glycolysis (the Warburg effect) and proliferation of ECs, which in turn leads to vascular remodeling and luminal narrowing. Meanwhile, infiltrating immune cellsundergo phenotypic polarization and functional alterations in response to stimulation of the AS microenvironment (hypoxia, inflammatory factor enrichment) and adapt to the energy demand through metabolic reprogramming (enhanced glycolysis, imbalance of fatty acid oxidation, FAO) to maintain their activation, proliferation, and inflammatory effects. However, such adaptive metabolic changes may exacerbate lipid phagocytosis and inflammatory responses, further promoting AS progression. Currently, key controversies remain in the therapeutic strategy of AS: should the therapeutic target of AS be centered oncorrecting vascular endothelial dysfunction or targeting the modulation of immune cell metabolic reprogramming? In addition, the causal relationship between the two has not been fully elucidated - is it endothelial dysfunction that triggers immune metabolic disorders, or is it the aberrant activation of immune cells that exacerbates endothelial damage? How do the two synergize to drive the cascade response in AS? In this article, the dynamic interplay between vascular endothelial dysfunction and immune-metabolic reprogramming in the development of AS will be systematically described and analyzed from the perspectives of molecular mechanisms and therapeutic targets, and case studies will be presented.